The economic impact by COVID-19 Pandemic in South Asia: Islamic economical tool based short and long term policy responses for South Asian Muslim countries / Muhammad Mostofa Hossain and Luqman Abdullah - Hossain, Muhammad Mostofa; Abdullah, Luqman (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The Covid-19pandemic has direly smacked over 200 countries, threatening a global economic growth that has adversely been peeved by the outbreak. It has patterned jeopardizes globally encompassing economic recession, probable high unemployment rate, mounting the poverty line and death of over 2.5 million people. Meanwhile, the second peak of the pandemic is infuriating many countries, which may result in around 13% to 32% projected global trade downgrade. Alike, the South Asian economy is suffering from a dire hit of the pandemic and undergoing an atrocious economical mishap. It resulted in a potential decline in the economy than in a normal downturn that materialised different rebounds in habitual succession. Islam safeguards all necessities to authenticate people’s wellbeing. Protecting ‘life’ and ‘wealth’ from those necessities mean securing the human being from natural and human-made shocks. Islam, therefore, represents a set of principles to exile the shocks like the Covid-19 pandemic. The paper aims to highlight the Islamic framework and policy responses using its financial tools to get rid of the pandemic crisis in South Asia especially in the Muslim countries of the reign.